Evaluation in teacher training in undergraduate courses in Mathematics (Research, Society and Development, 2020)
Evaluation is a didactic-pedagogical component that constitutes teaching work at the various levels and modalities of education in Brazil. The object of this research consisted of the evaluation of teaching and learning in the Degree in Mathematics, where an analysis of the evaluation proposals described in the Pedagogical Projects of the Courses (PPC) and in the Programs of the disciplines was carried out. The investigation, with a qualitative approach, used the case study method with a bibliographic and documentary collection technique. The theoretical-methodological foundation organized based on the studies of Hoffmann (2013), Luckesi (2011) and Tardif (2014), among others. The data revealed that the evaluation is linked to the autonomy of the university professor. Our study found gaps about the evaluation in one of the projects, due to the lack of the evaluation proposal, because it did not present a north about the evaluation for teachers, as well as for students.